MINERAL REACTIONS IN HIGH-ALUMINA FERRIFEROUS METAPELITIC HORNFELSES IN CONNECTION WITH THE PROBLEM OF STABILITY OF RARE PARAGENESES OF CONTACT METAMORPHISM - Likhanov I.I. (My University, 2003)
A detailed petrological study has been given to high-alumina ferriferous hornfelses characterized by the development of mineral associations (Cld + Bt, Cld + Bt + And, and Crd + Grt + Ms), quite rare for contact metamorphism. The sequence and stability of the observed parageneses were thoroughly analyzed in terms of the Harte-Hudson, Spear-Cheney, and Powell-Holland petrogenetic grids. It has been shown that in the contact aureole of the Ayakhta Massif: (1) the formation of chloritoid atypical of thermal metamorphism and the stability of rare parageneses (Cld + Bt and Cld + And + Bt) are explained by a rare combination of appropriate pressure (≥ 3 kbar) with a specific type of rocks enriched in both Al and Fe; (2) the appearance of the Grt + Crd + Ms paragenesis is caused by specific chemical compositions of Mn-enriched garnet and high-Al high-Fe rocks; (3) the development of Crd-And parageneses and staurolite-free associations at the intermediate steps of contact metamorphism is explained by the simultaneous expansion of the Grt + Chl field with participation of Mn-garnets and narrowing, up to complete disappearance, of the St + Bt stability field; (4) the sequence of the observed parageneses and reactions in high-Al Fe-rich hornfelses of the Ayakhta aureole is in agreement with the Spear-Cheney thermodynamic petrogenetic grid.
Keywords: Metapelites; chloritoid; mineral reactions; petrogenetic grids